Utilization of palliative care services and associated factors among cancer patients in Ethiopia: A systematic review and meta-analysis - Sadik Abdulwehab; Frezer Kedir (PLoS ONE, 2026)
Introduction Palliative care is vital for cancer management in low- and middle-income countries like Ethiopia, but underutilization leads to unmanaged symptoms and reduced patient quality of life, and fragmented studies hinder evidence-based planning and policy development. This systematic review and meta-analysis aim to synthesize existing literature to estimate the utilization rate of Palliative care among cancer patients in Ethiopia and to identify key influencing factors. Review method and data sources This study employed a systematic review and meta-analysis design to assess Palliative care utilization and its influencing factors among cancer patients in Ethiopia, sourcing evidence from various electronic databases until April 07, and studies published between 2015 and 2024 were included. The data was extracted from June 10–20 and analyzed from June 21–30, with report generation till July 27, 2025, using R software. Meta-analysis was performed using a random-effects model, with forest plots illustrating pooled prevalence and associated factors. Heterogeneity was assessed using the I² statistic, and study quality was evaluated by using a validated tool, the Joanna Briggs Institute Critical Appraisal Checklist. Results A total of nine cross-sectional studies involving 2,839 cancer patients were included. The pooled Palliative care utilization rate was 42% (95% CI: 30%–54%). Educational attainment (pooled AOR = 2.57; 95% CI: 1.42–3.75) and male gender (pooled AOR = 5.58; 95% CI: 3.01–10.33) were factors significantly associated with Palliative care utilization. Conclusion This review showed the Palliative care utilization rate was 42%. Palliative care utilization in Ethiopia remains insufficient, reflecting systemic, socioeconomic, and geographic inequities. Expanding access will require decentralization of services to reach rural communities, integration of Palliative care into primary healthcare, investment in workforce capacity, and improved patient and family awareness. Strengthening these areas is essential to ensure equitable, patient-centered, and sustainable Palliative care delivery in Ethiopia. PROSPERO registration number CRD420251027739.